2018
DOI: 10.1002/ece3.4666
|View full text |Cite
|
Sign up to set email alerts
|

Methuselah’s daughters: Paternal age has little effect on offspring number and quality in Cardiocondyla ants

Abstract: Male age may directly or indirectly affect the fitness of their female mating partners and their joint progeny. While in some taxa of insects, old males make better mates and fathers, young males excel in others. Males of most social Hymenoptera are relatively short lived and because of testis degeneration have only a limited sperm supply. In contrast, the wingless fighter males of the ant Cardiocondyla obscurior live for several weeks and produce sperm throughout their lives. Wingless males engage in lethal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 61 publications
0
5
0
Order By: Relevance
“…In contrast to negative effects of old fathers reported by studies, few studies report no effects of paternal age on offspring quality (Heinze et al, 2018;Sparks et al, 2022). Others yet show that old fathers can produce larger (Aguilar et al, 2023;Mirrhosseini et al, 2014;Pappert et al, 2023), longer lived (Angell et al, 2022;Johnson et al, 2018;Krishna et al, 2012;Lee et al, 2019;Priest et al, 2002), and more fecund (Krishna et al, 2012;Sparks et al, 2022) offspring than young fathers (also see Kroeger et al, 2020 for beneficial maternal age effects).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to negative effects of old fathers reported by studies, few studies report no effects of paternal age on offspring quality (Heinze et al, 2018;Sparks et al, 2022). Others yet show that old fathers can produce larger (Aguilar et al, 2023;Mirrhosseini et al, 2014;Pappert et al, 2023), longer lived (Angell et al, 2022;Johnson et al, 2018;Krishna et al, 2012;Lee et al, 2019;Priest et al, 2002), and more fecund (Krishna et al, 2012;Sparks et al, 2022) offspring than young fathers (also see Kroeger et al, 2020 for beneficial maternal age effects).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, old males across different species often have smaller ejaculate sizes (Cornwallis et al, 2014;Sanghvi et al, 2023), poorer quality sperm (Gasparini et al, 2019;Johnson et al, 2015), and lower abundance of seminal fluid proteins (Fricke et al, 2023), than young males. A growing body of literature however, challenges these patterns by documenting that advancing male age does not necessarily result in male reproductive senescence (Aich et al, 2022;Baudisch and Stott, 2019;Brooks and Kemp, 2001;Cooper et al, 2020Cooper et al, , 2021Finch, 2009;Forslund and Part, 1995;Heinze et al, 2018;Johnson and Gemmell, 2012;Jones et al, 2014;Jones and Vaupel, 2017;Lee and Chu, 2023;Moullec et al, 2023;Sandfoss et al, 2023;Segami et al, 2021;Vega-Trejo et al, 2019). In some cases, advancing age may even be associated with increased reproductive output (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, younger males having poorer ejaculate traits (e.g. Heinze et al, 2018;Lifjeld et al, 2022), smaller ejaculates (e.g. , and lower ferilisation success (Lifjeld et al, 2022) than older males.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies simply report no detectable effect of paternal age on offspring traits (e.g., ants: Heinze et al. 2018; fruitflies: Lee et al. 2019; monoandrous moth: Lai et al.…”
mentioning
confidence: 99%
“…On the other hand, some studies have shown that offspring fathered by older males have better early life and adult performance (e.g., fruitflies: Krishna et al 2012;Lee et al 2019;European blackbirds: Cholewa et al 2021), including a higher rate of early life survival (e.g., butterfly: Ducatez et al 2012;zebra fish: Johnson et al 2018;superb fairy-wren: Cooper et al 2020) and longevity (e.g., antler flies: Angell et al 2022). Other studies simply report no detectable effect of paternal age on offspring traits (e.g., ants: Heinze et al 2018;fruitflies: Lee et al 2019;monoandrous moth: Lai et al 2020;common gulls: Sepp et al 2021;burying beetle: Cope et al 2021). These equivocal findings about how a father's age affects offspring fitness raise concerns that there are confounding variables that mask any consistent, direct effect of male age on offspring fitness.…”
mentioning
confidence: 99%